Autoantibodies to MOG in a distinct subgroup of adult multiple sclerosis. Issue 5 (October 2016) - Spadaro, Melania; Gerdes, Lisa Ann; Krumbholz, Markus; Ertl-Wagner, Birgit; Thaler, Franziska Sabrina; Schuh, Elisabeth; Metz, Imke; Blaschek, Astrid; Dick, Andrea; Brück, Wolfgang; Hohlfeld, Reinhard; Meinl, Edgar; et al.
Abstract : Objectives: To evaluate the presence of antibodies to conformation-intact myelin oligodendrocyte glycoprotein (MOG) in a subgroup of adult patients with clinically definite multiple sclerosis (MS) preselected for a specific clinical phenotype including severe spinal cord, optic nerve, and brainstem involvement. Methods: Antibodies to MOG were investigated using a cell-based assay in 3 groups of patients: 104 preselected patients with MS (group 1), 55 age- and sex-matched, otherwise unselected patients with MS (group 2), and in 22 brain-biopsied patients with demyelinating diseases of the CNS (n = 19 with MS), 4 of whom classified as MS type II (group 3). Recognized epitopes were identified with mutated variants of MOG. Results: Antibodies to MOG were found in about 5% (5/104) of preselected adult patients with MS. In contrast, in groups 2 and 3, none of the patients tested positive for MOG antibodies. Patients with MS with antibodies to MOG predominantly manifested with concomitant severe brainstem and spinal cord involvement and had a severe disease course with high relapse rates and failure to several disease-modifying therapies. Three of them had been treated with plasma exchange with a favorable response. All anti-MOG–positive patients with MS showed typical MS lesions on brain MRI. Longitudinal analysis up to 9 years revealed fluctuations and reappearance of anti-MOG reactivity. Epitope mapping indicated interindividual heterogeneity, yet intraindividual stability of the antibody response. Conclusions: Antibodies to MOG can be found in a distinct subgroup of adult MS with a specific clinical phenotype and may indicate disease heterogeneity.